Analisis Kompetensi Sumber Daya Manusia Kantor Kecamatan Arjasa Kabupaten Sumenep - Syarif Efendi; Pardiman Pardiman; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Employees at the Arjasa District Office lack competence, resulting in Arjasa District Office employees often sleeping during working hours so that they are less than optimal in carrying out their work. This study aims to determine the competence of employees in carrying out public services at the Arjasa District Office. As well as to find out the factors that affect the competence of employees in carrying out public services at the Arjasa District Office and to find out what can increase the competence of employees at the Arjasa District Office. Methods In this study using a qualitative approach, by means of observation and interviews. This research is located at the Arjasa District Office, Kangean Islands, Sumenep Regency. With the increase in employee competence as well as increasing skills and knowledge of the Arjasa District Office employees will have an effect on improving performance. And because the Panisman has not been fully implemented, there are still employees who have not complied with the regulations. And lack of a good attitude resulting in a lack of enthusiasm at work and not complying with regulations in carrying out work and sleeping at work. Keywords: Competence, Arjasa District Office, Employee, performance.